Figure 8 from: Haukisalmi V, Konyaev S, Lavikainen A, Isomursu M, Nakao M (2016) Description and life-cycle of Taenia lynciscapreoli sp. n. (Cestoda, Cyclophyllidea). ZooKeys 584: 1-23. https://doi.org/10.3897/zookeys.584.8171 - Haukisalmi, Voitto; Konyaev, Sergey; Lavikainen, Antti; Isomursu, Marja; Nakao, Minoru (Zenodo, 2016)
Figure 8 - Pairwise comparisons of the shape of the large rostellar hooks in Taenia lynciscapreoli sp. n. and related species, using the junction between the blade and the guard as an anchor region for alignment. The hook of Taenia lynciscapreoli sp. n. is indicated by a black outline. A legend for measurements taken from the large hooks of the new species (Table 1) is also shown.